Radium‐223 Safety, Efficacy, and Concurrent Use with Abiraterone or Enzalutamide: First U.S. Experience from an Expanded Access Program. (28th November 2017) - Sartor, Oliver; Vogelzang, Nicholas J.; Sweeney, Christopher; Fernandez, Daniel C.; Almeida, Fabio; Iagaru, Andrei; Brown, Alan; Smith, Matthew R.; Agrawal, Manish; Dicker, Adam P.; Garcia, Jorge A.; Lutzky, Jose; et al.
Abstract : Background: In the phase III ALSYMPCA trial, metastatic castration‐resistant prostate cancer (mCRPC) patients had few prior life‐prolonging therapies. Following ALSYMPCA, which demonstrated radium‐223 survival benefit, and before radium‐223 U.S. commercial availability, an expanded access program (EAP) providing early‐access radium‐223 allowed life‐prolonging therapies in current use. Subjects, Materials, and Methods : This phase II, open‐label, single‐arm, multicenter U.S. EAP (NCT01516762) enrolled patients with symptomatic mCRPC, ≥2 bone metastases, and no lung, liver, or brain metastases. Patients received radium‐223 55 kBq/kg intravenously every 4 weeks × 6. Primary outcomes were acute and long‐term safety. Additional analyses were done by number of radium‐223 injections, and prior or concomitant abiraterone or enzalutamide use. Results: Of 252 patients, 184 received radium‐223: 165/184 (90%) had Eastern Cooperative Oncology Group (ECOG) performance status 0–1; 183 (99%) had prior systemic anticancer therapy. Treatment‐related adverse events occurred in 93/184 (51%) patients during treatment and 11 (6%) during follow‐up. Median overall survival was 17 months, with 134/184 (73%) patients censored because of short follow‐up due to radium‐223 approval. In post hoc analyses, patients with ≥3 prior anticancer medications, baseline ECOG performance status ≥2, and lower baseline hemoglobin were less likely to receive 5–6 radium‐223 injections and unlikely to benefit from radium‐223. Radium‐223 was well tolerated regardless of concurrent or prior abiraterone or enzalutamide. Conclusion : Radium‐223 was well tolerated, with no new safety concerns; safety was maintained with abiraterone or enzalutamide. Patients with more advanced disease were less likely to benefit from radium‐223. Clinicians should consider baseline characteristics and therapy sequence for greatest clinical value. Implications for Practice: In this phase II U.S. expanded access program, radium‐223 was well tolerated, with a median overall survival of 17 months in metastatic castration‐resistant prostate cancer patients. In post hoc analyses, radium‐223 was safe regardless of concurrent abiraterone or enzalutamide, and median overall survival appeared longer when radium‐223 was used earlier in patients with less prior treatment. Patients with more advanced disease were less likely to benefit from radium‐223. Clinicians should consider baseline clinical characteristics and therapy sequence to provide the greatest clinical value to patients. Abstract : This article presents safety and exploratory efficacy findings from a U.S. expanded access program. Additionally, subgroup analyses evaluating overall survival by number of radium‐223 injections and safety and overall survival by prior or concomitant abiraterone or enzalutamide are reported.